Limited genetic diversity among Sarcocystis neurona strains infecting southern sea otters precludes distinction between marine and terrestrial isolates - Wendte, J.M. (2009)
Sarcocystis neurona is an apicomplexan parasite identified as a cause of fatal neurological disease in the threatened southern sea otter (Enhydra lutris nereis). In an effort to characterize virulent S. neurona strains circulating in the marine ecosystem, this study developed a range of markers relevant for molecular genotyping. Highly conserved sequences within the 18S ribosomal gene array, the plastid-encoded RNA polymerase (RPOb) and the cytochrome c oxidase subunit 1 mitochondrial gene (CO1) were assessed for their ability to distinguish isolates at the genus and species level. For within-species comparisons, five surface antigens (SnSAG1-SnSAG5) and one high resolution microsatellite marker (Sn9) were developed as genotyping markers to evaluate intra-strain diversity. Molecular analysis at multiple loci revealed insufficient genetic diversity to distinguish terrestrial isolates from strains infecting marine mammals. Furthermore, SnSAG specific primers applied against DNA from the closely related species, Sarcocystis falcatula, lead to the discovery of highly similar orthologs to SnSAG2, 3, and 4, calling into question the specificity of diagnostic tests based on these antigens. The results of this study suggest a population genetic structure for S. neurona similar to that reported for the related parasite, Toxoplasma gondii, dominated by a limited number of successful genotypes.